Interpersonal communication between students and gurèe in instilling Islamic values: A case study of Dayah Mudi Mesra in Aceh, Indonesia - Arahman, Zulfikar; Abda, Yusfriadi; Bahri, Saipul; Darma, Satria (Islamic Communication Journal, 2025)
This study examines the interpersonal communication between students (santri) and teachers (gurèe) in instilling Islamic values at LPI Dayah Mudi Mesra, Aceh. The interpersonal communication between santri and gurèe is not limited to the transfer of knowledge but also involves a deep emotional relationship, playing a crucial role in the internalization of moral and spiritual values. This research uses a qualitative method with a case study approach, collecting data through in-depth interviews, participant observation, and documentation. The results show that intensive interpersonal communication serves as an effective medium in shaping the Islamic character of santri, with teachers acting as a role model and providing moral guidance through daily attitudes and behaviors. This relationship enables students to more easily internalize religious teachings in their daily lives. This study contributes to understanding the important role of interpersonal communication in dayah education, particularly in shaping santri with noble character and strong spirituality. Moreover, this study strengthens interpersonal communication rooted in Islamic values, setting it apart from conventional notions of interpersonal communication ***** Penelitian ini mengkaji komunikasi interpersonal antara santri dan gurèe (guru) dalam menanamkan nilai-nilai keislaman di Dayah Mudi Mesra. Komunikasi interpersonal antara santri dan Gurèe tidak hanya terbatas pada transfer ilmu, tetapi juga melibatkan hubungan emosional yang mendalam, yang berperan penting dalam internalisasi nilai-nilai moral dan spiritual. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus, mengumpulkan data melalui wawancara mendalam, observasi partisipan, dan dokumentasi. Hasil penelitian menunjukkan bahwa komunikasi interpersonal yang intensif menjadi sarana efektif dalam membentuk karakter islami santri, dengan Gurèe bertindak sebagai teladan yang memberikan bimbingan moral melalui sikap dan perilaku sehari-hari. Hubungan ini memungkinkan santri untuk lebih Mudih menginternalisasi ajaran agama dalam kehidupan sehari-hari. Kajian ini memberikan kontribusi terhadap pemahaman tentang peran penting komunikasi interpersonal dalam pendidikan di dayah, khususnya dalam membentuk karakter santri yang berakhlak mulia dan kuat secara spiritual. Lebih jauh, studi ini memperkuat komunikasi interpersonal yang berakar pada nilai-nilai keislaman, yang membedakannya dari konsep komunikasi interpersonal pada umumnya.